Distribution and Prevalence of Multidrug-Resistant Organisms (MDROs) Among MDRO-Positive Individuals at Dr. Kariadi Hospital - Saidi Ntambi; Dwi Sutiningsih; Maiga Ayub Hussein; Budi Laksono (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2023)
Background: Multidrug-resistant organisms (MDRO) pose a significant challenge to healthcare facilities globally, impacting patient outcomes and healthcare costs. Understanding the distribution and prevalence of MDRO is crucial for effective infection control and prevention strategies. This study aimed to investigate the distribution and prevalence of MDROs, among MDRO-positive individuals at Dr. Kariadi Hospital.Methods: A retrospective analysis of secondary data was conducted, encompassing a diverse range of MDROs, including ESBL, carbapenem-resistant Enterobacteriaceae (CRE), methicillin-resistant Staphylococcus aureus (MRSA), and vancomycin-resistant Staphylococcus aureus (VRSA). The study population consisted of individuals who tested positive for MDRO within the hospital.Results: A total of 100 MDRO-positive cases were identified during the study period. The most prevalent MDRO identified was ESBL-producing organisms, accounting for 59% of all cases. Other significant findings included the presence of carbapenem-resistant Enterobacteriaceae (CRE) and MRSA, which constituted 4% and 3% of the MDRO-positive cases, respectively. Notably, a diverse range of MDRO species, such as MRCoNS (methicillin-resistant coagulase-negative Staphylococci), was also detected.Conclusion: This study provides valuable insights into the distribution and prevalence of MDRO at Dr. Kariadi Hospital. The findings underscore the urgent need for robust infection control measures and targeted interventions to mitigate the spread of MDRO. Implementing effective surveillance, promoting antibiotic stewardship, and enhancing preventive strategies are crucial for controlling MDRO infections. Future research should focus on exploring the molecular characteristics and resistance mechanisms of the identified MDRO to inform tailored prevention and treatment approaches.Â